MODAL SOSIAL DALAM PENGELOLAAN FESTIVAL BUDAYA YANG BERKELANJUTAN (STUDI KASUS FESTIVAL KAMPUNG CEMPLUK) - Leny Suryani (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to analyze social capital in the management of sustainable cultural festivals, especially at the Kampung Cempluk festival in Malang. The success of managing the cempluk village festival is inseparable from the parties involved. The involvement of parties in the management of the cempluk village festival is a form of social capital. The more parties with similar values and the better social capital they have, the more effective and efficient it will be. This study uses a qualitative research method using a qualitative descriptive approach. Data collection techniques using interviews, observation, and documentation. Data were analyzed using data analysis techniques developed by Miles & Huberman. The results of the study show that three forms of social capital occur in the management of the Kampung Cempluk festival: (1) bonding social capital, which is manifested in the form of cooperation traditions, festivals as cultural holidays, different themes, and community involvement, (2) social bridging capital, manifested in the form of the archipelago village network (Japung Nusantara) and the sonjo kampung program, (3) linking social capital, which is manifested in the form of cooperation with universities, donors, sponsors, and the mass media.